Factors related to The incidence of preeclampsia in Sunan Kudus Hospital - Nia Ilhammatul Ulla; Noor Hidayah; Edy Soesanto (International Journal of Health and Pharmaceutical (IJHP), 2026)
Preeclampsia is one of the main causes of maternal morbidity and mortality in Indonesia which is characterized by increased blood pressure and impaired organ function after 20 weeks of gestation. This study aims to determine the relationship between diabetes mellitus, anemia, and the distance between pregnancies and the incidence of preeclampsia in pregnant women who give birth at Sunan Kudus Hospital in 2024. This study used a quantitative design with a retrospective case-control approach, involving 252 respondents consisting of 63 pregnant women with preeclampsia (cases) and 189 pregnant women without preeclampsia (control). Data were collected secondary through medical records and analyzed using the Chi-Square test with a 95% confidence level and p< significance of 0.05. The results showed that diabetes mellitus was not significantly associated with the incidence of preeclampsia (p = 0.096; OR = 2,737; CI 0.884–8.475), but mothers with DM have a 2.7-fold greater risk of developing preeclampsia. There was a significant association between anemia and the incidence of preeclampsia (p = 0.001; OR = 2,794; CI 1.520–5.136) and between the distance between pregnancy and the incidence of preeclampsia (p = 0.022; OR = 2,053; CI 1,146–3,679). In conclusion, anemia and the distance between pregnancies at risk have a meaningful relationship with the incidence of preeclampsia, whereas diabetes mellitus is not statistically significant but still has the potential to increase risk. Prevention of preeclampsia needs to be focused on monitoring hemoglobin levels, setting ideal pregnancy distances, and managing metabolic diseases during pregnancy through comprehensive antenatal care examinations.